2016
DOI: 10.1371/journal.pone.0150189
|View full text |Cite|
|
Sign up to set email alerts
|

DNA Sequence Determinants Controlling Affinity, Stability and Shape of DNA Complexes Bound by the Nucleoid Protein Fis

Abstract: The abundant Fis nucleoid protein selectively binds poorly related DNA sequences with high affinities to regulate diverse DNA reactions. Fis binds DNA primarily through DNA backbone contacts and selects target sites by reading conformational properties of DNA sequences, most prominently intrinsic minor groove widths. High-affinity binding requires Fis-stabilized DNA conformational changes that vary depending on DNA sequence. In order to better understand the molecular basis for high affinity site recognition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 71 publications
0
53
0
Order By: Relevance
“…Docking the Fis dimer successfully to its target involves an induced fit mechanism in which minor groove compression accompanied by bending of the target DNA accommodates the side-by-side protein monomers (Stella et al, 2010). Fis binding is influenced strongly by indirect readout and minor groove conformation (Hancock et al, 2016). Changing the supercoiling of the DNA also exerts an effect: Fis prefers DNA that is negatively supercoiled, a requirement that is easily met during the early stages of logarithmic growth when Fis is abundant.…”
Section: Discussionmentioning
confidence: 99%
“…Docking the Fis dimer successfully to its target involves an induced fit mechanism in which minor groove compression accompanied by bending of the target DNA accommodates the side-by-side protein monomers (Stella et al, 2010). Fis binding is influenced strongly by indirect readout and minor groove conformation (Hancock et al, 2016). Changing the supercoiling of the DNA also exerts an effect: Fis prefers DNA that is negatively supercoiled, a requirement that is easily met during the early stages of logarithmic growth when Fis is abundant.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple structure-function studies have focused on Escherichia coli Fis (referred to as EcFis) and have shown that it has a four-helix bundle structure and functions as a homodimer (Kostrewa et al, 1991;Osuna et al, 1991;Stella et al, 2010;Shao et al, 2008;Hancock et al, 2013Hancock et al, , 2016. The disordered or flexible N-terminal region is required for Hinmediated inversion.…”
Section: Introductionmentioning
confidence: 99%
“…The HTH region is strongly conserved, suggesting that the DNA-binding properties of Fis are conserved. Several DNA-bound structures suggest that EcFis initially recognizes DNA targets with intrinsically narrow minor grooves using the separation between the HTH motifs in the EcFis dimer as a ruler (Stella et al, 2010;Hancock et al, 2013Hancock et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Further, simultaneous studies on folding and binding have been reported in Mutsα, a DBP . Recently, the role of DNA sequence on change in its structure and affinity for binding of DBPs has been reported . In addition, the disorderness is often observed in protein‐DNA complexes and about half of the proteins are predicted to be disordered among eukaryotic transcription factors.…”
Section: Introductionmentioning
confidence: 99%
“…32 Recently, the role of DNA sequence on change in its structure and affinity for binding of DBPs has been reported. 33 In addition, the disorderness is often observed in protein-DNA complexes and about half of the proteins are predicted to be disordered among eukaryotic transcription factors. Intrinsically disordered regions generally facilitate binding and folding not only in protein-DNA but also in protein-RNA and protein-protein interactions.…”
Section: Introductionmentioning
confidence: 99%